1997
DOI: 10.1111/j.1432-1033.1997.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of The Aminoacyl‐tRNa Synthetase Family and The Organization of the Drosophila Glutamyl‐Prolyl‐tRNA Synthetase Gene — Intron/Exon Structure of the Gene, Control of Expression of the Two mRNAs, Selective Advantage of the Multienzyme Complex

Abstract: In Drosophila, glutamyl‐prolyl‐tRNA synthetase is a multifunctional synthetase encoded by a unique gene and composed of three domains: the amino‐ and carboxy‐terminal domains catalyze the aminoacylation of glutamic acid and proline tRNA species, respectively, and the central domain is made of 75 amino acids repeated six times amongst which 46 are highly conserved and constitute the repeated motifs [Cerini, C., Kerjan, P., Astier, M., Gratecos, D., Mirande, M. & Sémériva, M. (1991) EMBO J. 10, 4267–4277]. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
(59 reference statements)
2
14
0
Order By: Relevance
“…Overexpression of these motifs in transgenic flies resulted in a decrease of fertility (17). This result further supports the physiological importance of these motifs.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Overexpression of these motifs in transgenic flies resulted in a decrease of fertility (17). This result further supports the physiological importance of these motifs.…”
supporting
confidence: 77%
“…Although the EPRS repeats were not essential for the activity of the connected tRNA synthetase (8), overexpression of these repeats in Drosophila resulted in sterility (17). Similarly, a mutation of the gene for yeast Arc1p induced slow growth and cold sensitivity of the cell, although it was not essential for the activities of the bound tRNA synthetases (41).…”
Section: Fig 4 Interaction Of Eprs Repeated Motifs With N-terminal mentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of in vivo experimental approaches acutely hindered our understanding of the underlying mechanisms. The only experimental approach was previously reported in Drosophila (30). It was shown that overexpression of the repeated motifs that link GluRS and ProRS in Drosophila leads to a sterility of the transgenic flies.…”
mentioning
confidence: 99%